2022
DOI: 10.1093/cvr/cvac068
|View full text |Cite
|
Sign up to set email alerts
|

Association between BNT162b2 or CoronaVac COVID-19 vaccines and major adverse cardiovascular events among individuals with cardiovascular disease

Abstract: Aims Concern about the cardiovascular safety of coronavirus disease 2019 (COVID-19) vaccines among individuals with cardiovascular disease (CVD) may lead to vaccine hesitancy. We sought to assess the association between two COVID-19 vaccines, BNT162b2 and CoronaVac, and the risk of major adverse cardiovascular events (MACE) in individuals with established CVD. Methods and results We identified individuals with a history of CV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 35 publications
(45 reference statements)
1
25
0
1
Order By: Relevance
“…However, a recent study reported that patients with previous history of major adverse cardiac events (MACE) are not at higher risk of further MACE after mRNA (BNT162b2) and inactivated (CoronaVac) vaccinations. 56 We also excluded cases with a positive SARS-CoV-2 test before and within the study period to minimize bias. Both hemorrhagic stroke and thromboembolic event cases such as ischemic stroke could potentially be an result from SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, a recent study reported that patients with previous history of major adverse cardiac events (MACE) are not at higher risk of further MACE after mRNA (BNT162b2) and inactivated (CoronaVac) vaccinations. 56 We also excluded cases with a positive SARS-CoV-2 test before and within the study period to minimize bias. Both hemorrhagic stroke and thromboembolic event cases such as ischemic stroke could potentially be an result from SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…The results further support that the risk of MACE following BNT162b2 and CoronaVac COVID-19 vaccines in patients with HF is very low and are consistent with our earlier study of patients with coronary heart disease, cerebrovascular disease, peripheral vascular disease or cardiovascular surgery where no increased risk of MACE was detected after receiving BNT162b2 or CoronaVac. 24 …”
Section: Discussionmentioning
confidence: 99%
“… 25 The methodology was developed for event-dependent exposures and outcome events with a high risk of short-term mortality and had also been applied to many high-quality COVID-19 vaccine safety studies. 21 , 22 , 23 , 24 Other strengths include using a number of sensitivity analyses to test the robustness of our results, including the risk of hospitalization for HF, MACE and all hospitalization as the study outcomes, and having both BNT162b2, a mRNA vaccine and CoronaVac, an inactivated vaccine in our analyses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations